EFFECT OF STUDENT FACILITATOR AND EXPLAINING ON BATTERY MATERIAL ON RESULT OF STUDENTS KARSA MULYA - Farianata Turang; Sri Murwantini (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2014)
The model Student Facilitator and Explaining is one of cooperative learning which has the idea on how teacher was able to present or demonstrate the material in front of the student then to give them a chance to explain to their friends. The key of this model is all the materials demonstrated which basically presented. This research aims to find: the effect of the application of the Student Facilitator and Explaining learning model on the material To Identify Battery Construction on the study result of students of Kelas X Teknik Sepeda Motor SMK Karsa Mulya Palangka Raya in 2013/2014, which are: (1) to know the student’ study result by using Student Facilitator and Explaining (SFE) learning model, (2) to know student study result by using conventional learning (speech), (3) to know the student’ study result difference between the two models. Method used in this research is the experiment type PretestPosttest Control Group Design since on this design the population is divided into two groups randomly. The first group is the test unit to the model proposed and the second unit is the control unit. This research takes sample of students Kelas X Teknik Sepeda Motor with 22 students, which is then divided into 2 group as experiment class and control class. The research result shows that there is a difference on the two groups in terms of study result. The group with SFE got higher average score (75,90) than the other group ( 63,72).